(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Print, printing and printmaking has a long world history. In India printing and printmaking activities flourished around in 1556, when the Portuguese missionaries have imported the printing press from Lisbon, to spread out the Christian mythology amongst the Indian people. Here I have found some interesting facts related to the printmaking developments where the region of Gujarat has an importance to help out in one another way whether activities related to printing commercial textiles or establishing printing machineries or to reach and teach the printmaking to the people and so on. In this article I have tried to focus some facts related to my findings on how the region of Gujarat, the people of Gujarat, or the community in Gujarat has helped out in one or other way to establish the reputation to contribute for the development of printing and printmaking.